Sex Differences on Behavioural Risk Factors of Hypertension among Rural Community Dwellers, Nepal: A Cross-Sectional Survey - Sharma, Muna; Singh, Babita; Adhikari, Bibhav (Nepalese Heart Journal, 2025)
Background: The increase in hypertension in developing countries has been brought about by the increasing prevalence of risk factors, such as increased alcohol consumption, smoking, obesity, physical inactivity, and low fruit and vegetable intake. This study was conducted to assess gender differences in the prevalence of behavioural risk factors of hypertension. Methods: Study design was cross-sectional survey. Adults residing in the Parsauni Rural Municipality, were the study population. In-person interview was done using WHO STEPs questionnaire among 596 samples selected via PPS technique. Height, weight, waist circumference, and hip circumference were measured by health personnel following standard technique. BMI and waist–hip ratio were calculated using standard formula. The data was analyzed using SPSS version 20 (IBM SPSS). Results: Out of 596 respondents, a higher proportion of women were past smokers (13.9%), and a higher proportion of males were current tobacco users (14.2%). Only 38.5% of respondents attempted to quit smoking, of which 3.0% were female. Similarly, 29.0% were past and 20.1% were current alcohol users. Only 40.8% and 56.0% of respondents were involved in vigorous-intensity and moderate-intensity physical activity, respectively. Only 41.6% and 8.6% of respondents consumed vegetables and fruits daily, respectively. There was no association of alcohol consumption, physical activity, or fruit and vegetable consumption with respondents’ sex. The odds of diagnosed hypertension were high among females (1.242, p = 0.034). Due to the cross-sectional design, causal relationships cannot be established. Conclusions: Behaviour-related health risks such as physical inactivity, low fruit and vegetable consumption, tobacco and alcohol use, overweight and obesity, and high-risk waist-to-hip ratios are high in community people.